An empirical study on factors responsible for Rheumatic Heart Disease (RHD) and its severity levels amongst the Bhutanese populace - Lhendup, Karma; Penjore, Yeshey (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background and objectives: This paper is aimed at excavating the factors responsible for RHD events and vis-à-vis establishing severity levels of RHD patients referred to Jigme Dorji Wangchuck National Referral Hospital (JDWNRH) in Thimphu’s capital city of Bhutan. Methods: By taking notorious advantage of the data gathered over the past five years (2016-2020) from RHD patients across 20 districts of Bhutan, about 232 RHD patients are involved in this study recorded in JDWNRH by the Cardiology Department. Besides descriptive methods, multivariate linear regression models augmented by the multinomial logistic regression models had been applied to establish the causual links. Results: The findings revealed that RHD prevailed amongst the young populace of Bhutan, especially females. Variables like age, frequency of visits, number of diagnostics, levels of education and region had been found as predictors of RHD prevalence. Other socio-demographic factors like occupation and status of employment did not affect the RHD prevalence. The multinomial logistic regression results indicated that higher levels of education as an important factor for not making the patient fall into the category of ‘severe.’ Age has been constantly found to be a highly significant variable contributing to RHD events and a quadratic relationship is revealed between age and the severity of RHD. Conclusion and implications for translation: This study pigeonholed the significant factors responsible for RHD events and entailed severity levels by gender and age. The findings of this study also provide additional important insights into developing public health policies and programs.